2023
DOI: 10.1177/11206721221148952
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography and angiography in Alzheimer's disease and other cognitive disorders

Abstract: Aims The aims of this study were to analyze retinal and choroidal changes on optical coherence tomography (OCT) and OCT-Angiography (OCT-A) in Alzheimer's disease (AD) patients and compare them to other forms of major dementia. We also aimed to analyze the correlation between clinical severity of global cognitive deficiency assessed by the mini-mental state exam (MMSE) score and OCT/OCT-A parameters. Methods Retrospective cross-sectional evaluative study of AD, and age-and gender-matched patients with other de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 78 publications
0
4
0
1
Order By: Relevance
“…FAZ area was lager in comparison to HC [10,29,37]. Researchers have also found that correlations between SRCP and disease duration [23], degree of cognitive impairment [23,36,42,49], and brain parenchymal volume [50] in AD patients continue to manifest. Biscetti et al found that the retinal FD is correlated with the CSF Aβ42/t-tau ratio [43].…”
Section: Ad and Ad-induced Cognitive Impairmentmentioning
confidence: 98%
See 3 more Smart Citations
“…FAZ area was lager in comparison to HC [10,29,37]. Researchers have also found that correlations between SRCP and disease duration [23], degree of cognitive impairment [23,36,42,49], and brain parenchymal volume [50] in AD patients continue to manifest. Biscetti et al found that the retinal FD is correlated with the CSF Aβ42/t-tau ratio [43].…”
Section: Ad and Ad-induced Cognitive Impairmentmentioning
confidence: 98%
“…Some studies have shown that the fundus of AD patients are not significantly different from the HC [14,15]. Nevertheless, more studies have found that the thickness of multiple retinal layers is significantly lower in AD patients compared to HC, including whole retinal thickness [16][17][18][19][20], ganglion cell plexiform layer (GC-IPL) [1,16,19,21,22], ganglion cell complex (GCC) [23], outer retinal layer [24] and RNFL [16,17,19,23,[25][26][27][28][29]. There was also a significant reduction in choroidal thickness [10,11,[30][31][32][33][34].…”
Section: Ad and Ad-induced Cognitive Impairmentmentioning
confidence: 99%
See 2 more Smart Citations
“…В рамках исследования Atherosclerosis Risk in Communities (ARIC) продемонстрировано, что некоторые редкие аномалии сетчатки глаза могут предсказать снижение когнитивных способностей и возникновение деменции [23,24]. В недавнем исследовании было показано, что количественный анализ ОКТ может помочь дифференцировать БА от других видов деменции, а ОКТА -выявить микрососудистые изменения у пациентов с БА, представляющие собой новые потенциальные критерии дифференциальной диагностики [25].…”
Section: актуальностьunclassified